Establishment of uranium mining and processing operations in the context of sustainable development. - Ganguly, C.; Waggitt, P. (IAEA nuclear energy series ;, 2009)
Australia; Northern Saskatchewan, Canada; Alligators River; Alaska; Niger; Russian Federation; USSR; Germany; Hungary.